2012
DOI: 10.3233/wor-2012-0486-2487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and redesign of manual material handling in a vaccine production centre’s warehouse

Abstract: This study was conducted in a warehouse at a vaccine production centre where improvement to existing storage and working conditions were sought through the construction of a new refrigerated store section (2-8C°). Warehousing tasks were videotaped and ergonomics analysis tools were used to assess the risk of developing MSDs. Specifically, these tools were the Rapid Entire Body Assessment (REBA) and the NIOSH equation. The current plant layout was sketched and analyzed to find possible targets for improvement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…NIOSH equation has been used in many studies to evaluate manual handling of loads; their results were consistent with our study, and the values obtained were higher than the recommended limit (29,30). These studies used their results for redesigning workstations for manual handling of loads (31,32). In this study, the prevalence of LBP among workers was reported equal to 100%, and LBP intensity evaluated by VAS was equal to 68.8 ± 17.8 (disabling pain).…”
Section: Discussionsupporting
confidence: 87%
“…NIOSH equation has been used in many studies to evaluate manual handling of loads; their results were consistent with our study, and the values obtained were higher than the recommended limit (29,30). These studies used their results for redesigning workstations for manual handling of loads (31,32). In this study, the prevalence of LBP among workers was reported equal to 100%, and LBP intensity evaluated by VAS was equal to 68.8 ± 17.8 (disabling pain).…”
Section: Discussionsupporting
confidence: 87%
“…Two studies were surveys of risk assessment tools used by field professionals (Arezes et al, 2011; Dempsey et al, 2005). Four studies were evaluations of risk reductions after implementation of interventions (Bernardes, Wanderck, & Moro, 2012; Dormohammadi, Amjad Sardrudi, Motamedzade, Dormohammadi, & Musavi, 2012; Pires, 2012; Torres & Vina, 2012). Exposures to MSD risks using the RNLE in different working populations were investigated in 10 studies, including grocery stockers (Davis & Orta Anés, 2014), firefighters (Gentzler & Stader, 2010), preschool teachers (Grant, Habes, & Tepper, 1995), neighborhood pub workers (Jones, Strickfaden, & Kumar, 2005), fishermen (Kucera et al, 2008; Kuruganti & Albert, 2013), fish processing workers, cooks (Xu & Cheng, 2014), workers in a fire brick manufacturing plant (Chung & Kee, 2000), and workers in many manufacturing and distribution sectors (Ciriello & Snook, 1999; Dempsey, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Ergonomic interventions were carried out recently to reduce MSD risk factors in such major economic sectors as manufacturing, the tobacco industry, tourism, the pharmaceutical industry, and the biotechnological industry [26][27][28][29][30][31]. These investigations have used film analysis techniques, process simulation, software to In addition, anthropometric data on the Cuban population have been used in the studies to determine optimal workplace dimensions [32].…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…Low-level symptoms of musculoskeletal disorders were detected in 73 percent of the workers surveyed; the symptoms were located in the neck, shoulders, and lower back. The percentage of positive critical behaviors by the workers increased to 65 percent from a reference level of 52 percent.Torres et al, 2010[27] Rodríguez and Pérez, 2011[31] Torres and Viña, 2012[28] The study was done in a pharmaceutical production facility. Three work stations were selected from a packing line, to evaluate extreme working postures and movements.…”
mentioning
confidence: 99%